2018
DOI: 10.1111/josi.12275
|View full text |Cite
|
Sign up to set email alerts
|

Media Violence and the General Aggression Model

Abstract: The General Aggression Model (GAM) is a meta-theory that considers the role of personal and situational variables on aggressive behavior, ranging from the biological to the cultural. Possible mediating variables include internal states (e.g., aggressive thoughts, angry feelings, increased physiological arousal) and the results of appraisal and decision processes (automatic and controlled). In this article, we focus on one situational variable-exposure to violent media-and how it can influence a wide array of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
152
2
8

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 94 publications
(97 reference statements)
17
152
2
8
Order By: Relevance
“…The GAM suggests that aggressive priming occurs when individuals are exposed to VVGs and also causes a short‐term increase in the accessibility of aggressive knowledge structures (such as aggressive beliefs and attitudes and aggressive schemata). These aggressive knowledge structures can increase individuals’ hostile attributions (Anderson & Bushman, ; Calvert et al, ). Thus, interpreting a situation in a hostile manner can increase anger, which in turn can increase aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The GAM suggests that aggressive priming occurs when individuals are exposed to VVGs and also causes a short‐term increase in the accessibility of aggressive knowledge structures (such as aggressive beliefs and attitudes and aggressive schemata). These aggressive knowledge structures can increase individuals’ hostile attributions (Anderson & Bushman, ; Calvert et al, ). Thus, interpreting a situation in a hostile manner can increase anger, which in turn can increase aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, priming effects should only play a role in very close temporal proximity to gameplay, and it is, therefore, difficult to observe the effects of VVGs on individuals’ aggressive behaviors over a longer period of time (e.g., >15 min). The repeated short‐term effects of VVGs could, therefore, elicit long‐term effects by developing aggressive knowledge structures (Allen et al, ; Anderson & Bushman, ; Calvert et al, ; Riva et al, ). These long‐term effects should occur over a long period of time due to the small effect size of VVGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Executive functions are higher order cognitive abilities that are responsible for the regulation of thoughts, emotions, and actions [36,37]. While there are many different ways to define or describe executive functioning, it is generally thought to comprise (1) cognitive control of planning or organizing action(s), (2) monitoring a series of responses [38][39][40], (3) divided attention or attentional control, (4) abstract reasoning, (5) alertness, and importantly, (6) behavioral regulation or inhibition [41][42][43]. A recent study that used a behavioral assessment of reactive aggressive behavior (i.e., an emotion-driven impulsive act in response to a perceived threat) found that the degree to which a participant could inhibit their responses (also known in cognitive psychology as "response inhibition") was the strongest predictor of reactive aggression.…”
Section: Executive Functions and Early Aversive Environmentsmentioning
confidence: 99%